Tourisme, mobilités et développement régional dans les Alpes Suisses: mise en scène et valeur territoriale. Montreux, Finhaut et Zermatt du XIXe siècle à nos jours - Guex, Delphine (Editions Alphil Presses universitaires suisses, 2016)
Through the paths of three resorts, this book examines how the areas af-fected by tourism and mobility change, and questions the notion of territorial value. The development of territories is understood through their mobility: the mobility not only of people but also of knowledge and information, as well as markets. Today, in a "hypermobile" world, places must be connect-ed. These networks lead to a standardization of territories. However, to at-tract tourists, media attention, and investors, territories must stand out! It is this process of staging and construction of value that this book presents.